The Meaning and Symbols of the Batak Karo Ethnic Ritual Ceremony: Study of Semiotics - Jekmen Sinulingga; Flansius Tampubolon (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to describe the meaning and symbol of the Cawir metua ritual ceremony, namely the death ceremony for the Karo community in Seberaya village, Karo district, North Sumatra Province. The method used in this research is a qualitative descriptive method which is done by collecting data by observation and interviews; descriptions that are bold and deep in nature, working with key informants. The theoretical framework used is the Social Semiotics approach, which is to interpret language in the sociocultural context in which culture is interpreted in semiotic terms as an information system. Based on the research that has been done, the authors obtained the results of the research, namely the symbolic meaning of the Cawir metua ceremony is the existence of symbols that have philosophical meanings in the Cawir metua ceremony.are still poor and need to be improved.